2006
DOI: 10.1007/s10459-006-9040-4
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Interactions and their Collaborative Reflection Processes during Peer Meetings

Abstract: Abstract. Teachers' reflections are often narrowly focused on technical questions ('how to') and less on the underlying moral, political and emotional aspects of their functioning. However, for a better understanding of teaching practice it is important to uncover beliefs and values that usually remain implicit. Meeting with others is considered crucial for enhancing the quality of teachers' reflections. However, little is known about how any beneficial effects of such meetings are brought about. We explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
2
28
0
1
Order By: Relevance
“…Adding peer group reflection resulted in deeper critical reflection and more concrete plans for change. These findings are in line with other studies (DeNisi & Kluger 2000;Steinert & Mann 2006;Tigelaar et al 2008;Mcleod & Steinert 2009;Schaub-de Jong et al 2009) which showed that a limited effect of individual self-reflection can be enhanced by peer meetings. However, no previous studies have compared strategies that differed only in the inclusion of a peer meeting.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Adding peer group reflection resulted in deeper critical reflection and more concrete plans for change. These findings are in line with other studies (DeNisi & Kluger 2000;Steinert & Mann 2006;Tigelaar et al 2008;Mcleod & Steinert 2009;Schaub-de Jong et al 2009) which showed that a limited effect of individual self-reflection can be enhanced by peer meetings. However, no previous studies have compared strategies that differed only in the inclusion of a peer meeting.…”
Section: Discussionsupporting
confidence: 93%
“…This problem can be overcome by facilitating feedback (Sargeant et al 2008) so as to stimulate feedback recipients to engage in constructive reflection on their practice (DeNisi & Kluger 2000;Smither et al 2005). Self-assessment and peer meetings are ways to facilitate feedback (Ross & Bruce 2007;Tigelaar et al 2008) and several authors have highlighted their importance in facilitating teachers' professional growth (Ross & Bruce 2007;Tigelaar et al 2008;Mcleod & Steinert 2009;Schaub-de Jong et al 2009;Stalmeijer et al 2009). There are, however, no published studies comparing the impact of different feedback strategies on the quality of self-reflection.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the increase of reflective behaviour and self-efficacy one might assume that this might indeed be attributed to the development programme, the more so because these results are supported by the results of the qualitative part of this study. It is also in line with previous research which reveals that reflective behaviour is promoted through interactions and peer group meetings (Schaub-de Jong, Cohen-Schotanus, Tigelaar, Dolmans, Meijer, Grave, & Vleuten, 2008). The multiple modules approach might have been very helpful again in building self-efficacy.…”
Section: Discussionsupporting
confidence: 88%
“…In the educational literature and in literature on knowledge management, different words are employed for concepts that have many similarities, or the same word is applied for notions that have little in common (Cox 2005). Learning networks (Koper et al 2005), learning communities (Ferguson et al 2009;Wood 2007), knowledge communities (Hakkarainen et al 2004), communities of practice (Wenger et al 2002), peer meetings (Tigelaar et al 2008) and critical companionship (Baguley and Brown 2009;Wright and Titchen 2003) appear for groups of different sizes, in different contexts like education and business, with or without explicit learning objectives. Nevertheless, most of these concepts encompass discussion among peers, with the purpose of sharing knowledge and constructing meaning socially.…”
Section: Learning Communitiesmentioning
confidence: 99%